A Statistical Portrait of the Resistance to Logic by Sunni Muslim Scholars Based on the Works of Jalāl al-Dīn al-Suyūtī (849-909/1448-1505) - Ali, Mufti (Islamic law and society, 2008)
Abstract On the basis of my analysis of four works composed by al-Suyūtī, I argue that hostility to logic was a predominant feature of Sunni scholarship, especially during the 13th, 14th, and 15th centuries. Logic was condemned by distinguished Sunni scholars in Valencia, Fez, Aleppo, Iraq, and Mecca, but especially in Egypt and Syria. This conclusion confirms Goldziher's argument that resistance to logic started already in the 2nd/8th century and increased in the 13th and 14th centuries; and disconfirms al-Rouayheb's argument that opposition to logic was never predominant among Muslim Sunni scholars.